Temperature-Controlled Synthesis of Thiophenol-VBXs from EBXs and Thiophenols - Li, Jun; Zhou, Chuang; Chen, Lian-Mei; Chen, Xing-Yu; Guo, Xiao-Qiang; Kang, Tai-Ran (Synlett, 2024)
Vinylbenziodoxolones (VBXs) are important electrophilic alkene synthons. However, the synthesis of cis-thiophenol-VBX reagents from ethynylbenziodoxolones (EBXs) and thiophenols remains challenging. Herein, we explore an efficient method for the synthesis of cis-thiophenol-VBXs in excellent yield with excellent regio- and stereoselectivities from EBXs and thiophenols under temperature-controlled conditions.
Keywords: vinylbenziodoxolones; ethynylbenziodoxolones; iodine(III); thiophenols; temperature control